An analysis of the compliance approach used by revenue authorities with specific reference to case selection and risk profiling - Nel, M J (Rhodes University, Faculty of Commerce, Department of Accounting, 2005)
The vision of probably all revenue authorities is to promote compliance with the provisions of the taxation laws and to ensure responsible enforcement by the revenue authorities, thereby contributing to the economic well being of the country. As with virtually all revenue authorities the South African Revenue Services has to a large extent implemented the self-assessment approach to tax assessments. Because this system depends on this process of selfassessment, an effective risk-based audit approach is required to ensure that tax compliance and responsible enforcement is adhered to. An effective case selection methodology is required for revenue authorities to make informed choices on how best to direct their activities in order to address areas of greatest risk. Given these imperatives, the purpose of this study is to examine the case selection methodologies used by certain revenue authorities, including the South African Revenue Services, and to focus on the key elements of case selection: the use of computerised database systems, industry profiles, third party data and the role of the risk profiler. The results of the study indicate that the case selection methodology of the South African Revenue Services is lacking in some areas. Computerised risk analysis is limited to a certain classes of taxpayers and other aspects of concern are also highlighted in this study.
Keywords: Uncatalogued